Family Support and Quality of Life of Children with Cancer : A Cross-sectional Study - Gannika, Lenny; Mulyadi, Mulyadi; Simanjuntak, Susi Roida (Universitas Airlangga, 2025)
Introduction: This study aims to examine the relationship between family support and the quality of life of children with cancer. Methods: This study used a cross-sectional design. The population in this study were children diagnosed with cancer who were getting treatment at the hospital, as well as their parents who cared for them. The sampling technique was consecutive sampling with a total sample of 51 children and 51 parents. Data was collected through a questionnaire consisting of two parts, namely the child's quality of life scale using PedsQLTM 4.0 and PedsQLTM 3.0 Cancer Module and family support using the family support questionnaire. Data analysis was performed using the Pearson correlation test. Results: The study showed that there was a relationship between family support and the quality of life of children with cancer using both the general child quality of life scale (p = 0.001) and with the quality-of-life scale specifically for children with cancer (p < 0.001). Children who received greater family support tended to have a better quality of life compared to children with lower family support. Conclusion: Families play an important role in improving the quality of life of children with cancer. It is important to involve families in the child's care process and to provide education on the importance of family support. Future research should explore other associated factors and family interventions to improve the quality of life of children with cancer.